Task-dependent calibration of auditory spatial perception through environmental visual observation - Tonelli, Alessia; Brayda, Luca; Gori, Monica (Frontiers in Systems Neuroscience, 2015)
Visual information is paramount to space perception. Vision influences auditory space estimation. Many studies show that simultaneous visual and auditory cues improve precision of the final multisensory estimate. However, the amount or the temporal extent of visual information, that is sufficient to influence auditory perception, is still unknown. It is therefore interesting to know if vision can improve auditory precision through a short-term environmental observation preceding the audio task and whether this influence is task-specific or environment-specific or both. To test these issues we investigate possible improvements of acoustic precision with sighted blindfolded participants in two audio tasks (minimum audible angle and space bisection) and two acoustically different environments (normal room and anechoic room). With respect to a baseline of auditory precision, we found an improvement of precision in the space bisection task but not in the minimum audible angle after the observation of a normal room. No improvement was found when performing the same task in an anechoic chamber. In addition, no difference was found between a condition of short environment observation and a condition of full vision during the whole experimental session. Our results suggest that even short-term environmental observation can calibrate auditory spatial performance. They also suggest that echoes can be the cue that underpins visual calibration. Echoes may mediate the transfer of information from the visual to the auditory system.